Strategic management and performance measurement - Manojlović, Romea (Mednarodna revija za javno upravo, 2017)
The paper examines the link between strategic management and performance measurement in the public sector. The main hypothesis is that the stages of strategic management development are positively correlated with the number of performance dimensions measured by public organizations. In order to examine the stated hypothesis results from the empirical research conducted in Croatian public administration are being presented. A questionnaire has been sent to 253 central and local organizations and additional interviews have been conducted. The results confirm the hypothesis and determine that the enhancement of strategic planning and management is one of the main stimuli for performance measurement in Croatia.
Keywords: Croatia; Hrvaška; javna uprava; management; planiranje; planning; public administration; strategic management; strateški management